1981
DOI: 10.1111/j.1365-2222.1981.tb01608.x
|View full text |Cite
|
Sign up to set email alerts
|

Human antibodies against antigens of the sparrow, blackbird, weaver finch, canary, budgerigar, pigeon and hen using the indirect immunofluorescent technique

Abstract: Detection of antibodies against various birds, particularly against exotic birds, can be facilitated using the sensitive immunofluorescent technique on avian fixed-intestine cryostat sections. Different fluorescent patterns corresponding to difTerent human anti-avian antibodies have been observed. Sixty of IOO human sera containing antibodies against one avian species, predominantly pigeon, reacted also with all other avian species intestines; the remaining forty were more specific and reacted with a few speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 5 publications
1
12
0
1
Order By: Relevance
“…Of note, several amino acid residues highly conserved only among birds were observed in the N-terminal domain (Additional file 3: Figure S3). This specificity to birds may explain the cross-reactivity of patient sera to other unexposed avian species [24]. Our result is therefore consistent with the speculation from Mcsharry et al that immunoglobulin light chain may cause the BRHP.…”
Section: Discussionsupporting
confidence: 92%
“…Of note, several amino acid residues highly conserved only among birds were observed in the N-terminal domain (Additional file 3: Figure S3). This specificity to birds may explain the cross-reactivity of patient sera to other unexposed avian species [24]. Our result is therefore consistent with the speculation from Mcsharry et al that immunoglobulin light chain may cause the BRHP.…”
Section: Discussionsupporting
confidence: 92%
“…The sera of many avian species have proteins with antigenic identity [ 65, 66] which could explain the positive precipitin reactions to pigeon serum in subjects with exposure to other avian species, or in patients with inflammatory bowel disease e.g. coeliac disease in which serum antibody against avian antigens is caused by immune responses to ingested hens' egg proteins [ 66].…”
Section: Disease Spectrum Associated With Pigeonsmentioning
confidence: 99%
“…One of our patients, who started with asthma due to her budgerigar at the age of 42 and subsequently developed egg allergy, was ex clusively sensitized against bird feathers, egg-white and egg-yolk proteins, and made us aware that a simi lar cross-reactivity might exist for hen's eggs and other avian antigens. Indeed IgG antibodies against egg-yolk proteins have been described in workers ex posed to egg spray [13,14,30] and recent research on extrinsic allergic alveolitis (pigeon's breeder lung) demonstrated cross-reactivity of precipitating anti bodies to bird antigens among several species [19,20] and with the water-soluble egg-yolk proteins known as 'livetins' [21][22][23]. However, only 1 patient with asthma was recently reported to have parrot-specific IgE antibodies cross-reacting with crude egg-yolk ex tracts [24], The present paper describes the results obtained in 59 atopic adults systematically skin tested with budgerigar and canary feathers, egg white, egg yolk and pure livetin extracts and all the common pneumo-allergens.…”
Section: Introductionmentioning
confidence: 99%